Improving Functional Outcomes for Vascular Amputees Through Use of Mirror Therapy and Elimination of the Effects of Electromagnetic Fields. Issue 1 (2nd January 2016) - Houston, Helen; Dickerson, Anne E.
ABSTRACT: The objective of this pilot study was to investigate the effectiveness of combining an amputee limb cover to eliminate the effects of electromagnetic fields (i.e., pain) and a Mirror Therapy exercise program to improve functional outcomes for vascular amputees. A cross-sectional repeated-measures design was used with 14 participants with either acute amputations or surgery at least 8 to 24 months previously. The 4-week intervention included the use of an amputee limb cover and mirror therapy exercises each day. The outcome measures were activities of daily living interference (e.g., self-care, walking, car transfer, low chair transfer, sleep ), and well-being (e.g., satisfaction, mood, quality of life ) at three times (pre- and posttreatment and maintenance). Participants with acute amputations made significant improvements in the areas of self-care, walking, car transfer, sleep, mood, and quality of life, while the subacute participants improved significantly in sleep and satisfaction . A reduction in the time required before prosthetic fitting decreased from 12 weeks to 8 weeks for acute amputees and an improvement in wearing tolerance from 0–2 to 8–12 hours for the subacute amputees were unexpected results suggesting the combined intervention may improves the extent to which amputees can increase participation in their activities of everyday living.